2020
DOI: 10.1186/s12861-020-00213-5
|View full text |Cite
|
Sign up to set email alerts
|

The functions of ocu-miR-205 in regulating hair follicle development in Rex rabbits

Abstract: Background Hair follicles are an appendage of the vertebrate epithelium in the skin that arise from the embryonic ectoderm and regenerate cyclically during adulthood. Dermal papilla cells (DPCs) are the key dermal component of the hair follicle that directly regulate hair follicle development, growth and regeneration. According to recent studies, miRNAs play an important role in regulating hair follicle morphogenesis and the proliferation, differentiation and apoptosis of hair follicle stem cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that there is a direct relationship between the Notch signal pathway and hair follicle morphogenesis (Lin et al, 2000), high expression of Notch1 and Notch2 can accelerate the formation of mouse hair substrate, and at the same time, it can inhibit the cells around the hair substrate to form substrate (Crowe et al, 1998). Ocu-miR-205 can promote the transition of Rex rabbit hair follicles from the growing stage to a degenerative quiescent stage by regulating the expression of related genes and proteins in Notch, BMP, and other signaling pathways, to change the hair density (Liu et al, 2020). Krieger used a mouse model to study the regulation of the NF-kappa B signaling pathway in the hair follicle cycle and found that the NF-kappa B signaling pathway is essential for the growth and activation of hair follicle stem cells (Krieger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there is a direct relationship between the Notch signal pathway and hair follicle morphogenesis (Lin et al, 2000), high expression of Notch1 and Notch2 can accelerate the formation of mouse hair substrate, and at the same time, it can inhibit the cells around the hair substrate to form substrate (Crowe et al, 1998). Ocu-miR-205 can promote the transition of Rex rabbit hair follicles from the growing stage to a degenerative quiescent stage by regulating the expression of related genes and proteins in Notch, BMP, and other signaling pathways, to change the hair density (Liu et al, 2020). Krieger used a mouse model to study the regulation of the NF-kappa B signaling pathway in the hair follicle cycle and found that the NF-kappa B signaling pathway is essential for the growth and activation of hair follicle stem cells (Krieger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These lncRNAs and genes might play crucial roles in regulating hair follicle density, and their differential expression might be the reason for differences in hair follicle density and wool production between HWP and LWP rabbits. Liu et al (2020) analysed the miRNA effect on hair follicle density in the Rex rabbit [37], but lncRNA related to hair density in rabbits has only been done in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…These lncRNAs and genes might play crucial roles in regulating hair follicle density, and their differential expression might be the reason for differences in hair follicle density and wool production between HWP and LWP rabbits. Liu et al (2020) analysed the miRNA effect on hair follicle density in the Rex rabbit [ 35 ], but lncRNA related to hair density in rabbits has only been done in the present study.…”
Section: Discussionmentioning
confidence: 98%